Case report: Surgery combined with extracorporeal membrane oxygenation for a patient with type A aortic dissection complicated with myocardial infarction after percutaneous coronary intervention - Yu, Junjian; Yu, Wenbo; Zeng, Hui; Gao, Jianfeng; Xiong, Jianxian (Frontiers in Cardiovascular Medicine, 2023)
Background: Aortic dissection(AD) is a severe cardiovascular disease characterized by aortic rupture, insufficiency, aortic branch lumen stenosis, and occlusion. Acute ST-segment elevation myocardial infarction may be the primary manifestation when aortic dissection affects the coronary artery, leading to delayed or missed diagnosis of aortic dissection, preventing patients from receiving timely and comprehensive treatment. Simultaneous aortic repair and coronary artery bypass grafting surgery are controversial because their high mortality rates. Personalized and optimal treatment plans for patients should be taken seriously based on their different conditions and treatment options. Case presentation: A 42-year-old male who experienced 1 hour of persistent precordialgia was admitted to a local second-level hospital for emergency treatment. Electrocardiogram (ECG) showed evidence of ST-segment elevation and myocardial enzymes: CK-MB 18.35 ng/mL, troponin 0.42 ng/mL, The patient was treated for acute myocardial infarction (AMI) and urgently sent to the interventional catheter room. Coronary angiography showed stenosis of the starting part of the right coronary artery trunk. Thus, stent implantation was performed, and the stenosis section recovered patency, however, postoperative precordialgia was not alleviated. Computed tomography angiography (CTA) revealed a type A AD. The patient was immediately transferred to a higher-level hospital and underwent emergency surgery with cardiopulmonary bypass (CPB) ascending aorta replacement and the SUN’s procedure (total arch replacement and stented elephant trunk implantation), simultaneous implantation of extracorporeal membrane oxygenation(ECMO), and regained consciousness with in intensive care unit care. ECMO was discontinued when hemodynamics stabilized. The patient ultimately recovered well and was discharged. Conclusion: This case demonstrated that precordialgia is not limited to myocardial infarction but may also be accompanied by aortic dissection. Percutaneous coronary intervention (PCI) can timely and effectively restore coronary artery perfusion, strive for the opportunity of aortic repair surgery, and must be prepared to overcome pump failure caused by myocardial infarction, cardiopulmonary bypass, heart block time, and myocardial ischemia-reperfusion injury. Personalized treatment is crucial for patients with complex type A aortic dissection.